Parody of Malaysian life: the effects of Mat Luthfi’s video blogs (V-blogs) on Malaysian youth - Jalal Abidin, Jahira; Mohamed, Shafizan (Vibus Innovative Publishing Solutions, 2018)
This study intends to understand the effect of localized parody videos on youths. By specifically focusing on how young Malaysians respond to Mat Luthfi, a famous Malaysian vlogger, the study explicates how video parodies could become a source of entertainment, information and even patriotism. The ideas of user generated content and remix culture are referred to in order to put the youths’ viewing experience into context. Interviews were conducted with students at the International Islamic University Malaysia (IIUM), qualitative analysis was applied to make sense of the respondents experiences. In short, the study found that the youths were very much entertained by Mat Luthfi’s videos. More importantly they had positive impressions of the messages embedded in the parody videos. Among others, the respondents identified messages of racial unity, humanity and positive attitude.